Public speaking in a second language fear not - Dowling, Robert J.; Steinbach, Susan; Seabright Group (Davis, Calif. : The Seabright Group, 2005)
This video is designed for non-native speakers of English who need practice in pitch, intonation, voice projection, syllable stress, pronouncing numbers and percentages correctly. Tips are given for connecting with a Western audience. Building confidence in a second language is emphasized throughout the video, which ends with an informative speech modeling the skills taught.
Title from title screen.
Presenter: Susan Steinbach.
DVD format.
Keywords: English language -- Study and teaching -- Foreign speakers; Public speaking; Interpersonal communication; Communication and culture; Communication -- Study and teaching -- foreign speakers